The Effectiveness of Audiovisual Media on Students’ Listening Comprehension of Inspirational Stories at Ban Yaning School Narathiwat Thailand - Nadilah Tambunan; Khatib Lubis; Lili Herawati Parapat; Husniah Ramadhani Pulungan; Nur Afifah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study aims to analyse the effectiveness of audiovisual media on students’ ability to listen to inspirational stories at Ban Yaning School, Narathiwat, Thailand. Students’ low levels of focus and comprehension in listening lessons, which are still dominated by conventional methods, lead to difficulties in understanding story details and cause-and-effect relationships. The study employed a quantitative approach using a quasi-experimental design with a nonequivalent control group, utilising pre-test–post-test measurements. The research subjects comprised Year 7 as the control group (n=17) and Year 8 as the experimental group (n=18). The intervention was conducted over four sessions (two weeks) with a duration of 2×45 minutes per session. The research instrument consisted of a multiple-choice test to measure listening comprehension. The results showed an improvement in listening skills in both groups. The mean score of the control group increased from 58.65 to 81.82 (an increase of 23.18 points), whilst the experimental group increased from 59.50 to 82.89 (an increase of 23.39 points). Inferential analysis using ANCOVA with control for baseline scores indicated that the difference in final achievement between the groups was not significant; thus, audiovisual learning has not yet been proven to be superior to conventional learning over this duration of intervention. Analysis of the indicators revealed a more pronounced improvement in the aspects of detailed information (±45%), sequence of events (±43%), and cause and effect (±42%), whilst the lowest improvement was observed in the message indicator (±35%). These findings confirm that structured listening exercises improve listening skills, whilst the use of audiovisual media needs to be combined with active processing tasks to ensure a more balanced impact.